Comprehensive Adolescent Health Programs That Include Sexual and Reproductive Health Services: A Systematic Review - Kågesten, Anna (Am J Public Health, 2014)
We systematically reviewed peer-reviewed and gray literature on comprehensive adolescent health (CAH) programs (1998–2013), including sexual and reproductive health services. We screened 36 119 records and extracted articles using predefined criteria. We synthesized data into descriptive characteristics and assessed quality by evidence level. We extracted data on 46 programs, of which 19 were defined as comprehensive. Ten met all inclusion criteria. Most were US based; others were implemented in Egypt, Ethiopia, and Mexico. Three programs displayed rigorous evidence; 5 had strong and 2 had modest evidence. Those with rigorous or strong evidence directly or indirectly influenced adolescent sexual and reproductive health. The long-term impact of many CAH programs cannot be proven because of insufficient evaluations. Evaluation approaches that take into account the complex operating conditions of many programs are needed to better understand mechanisms behind program effects.